Motivational interviewing competencies among UK family nurse partnership nurses: a process evaluation component of the building blocks trial. Issue 1 (December 2016) - Channon, Sue; Bekkers, Marie-Jet; Sanders, Julia; Cannings-John, Rebecca; Robertson, Laura; Bennert, Kristina; Butler, Christopher; Hood, Kerenza; Robling, Michael
Abstract Background Motivational Interviewing (MI) is a person-centred counselling approach to behaviour change which is increasingly being used in public health settings, either as a stand-alone approach or in combination with other structured programmes of health promotion. One example of this is the Family Nurse Partnership (FNP) a licensed, preventative programme for first time mothers under the age of 20, delivered by specialist family nurses who are additionally trained in MI. The Building Blocks trial was an individually randomised controlled trial comparing effectiveness of Family Nurse Partnership when added to usual care compared to usual care alone within 18 sites in England. The aim of this process evaluation component of the trial is to determine the extent to which Motivational Interviewing skills taught to Family Nurse Partnership nurses were used in their home visits with clients. Methods Between July 2010 and November 2011, 92 audio-recordings of nurse-client consultations were collected during the 'pregnancy' and 'infancy' phases of the FNP programme. They were analysed using The Motivational Interviewing Treatment Integrity (MITI) coding system. Results A competent level of overall MI adherent practice according to the MITI criteria for 'global clinician ratings' was apparent in over 70 % of the consultations. However, on specific behaviours and the MITI-derived practitioner competency variables, there was a large variation in the percentage of recordings in which "beginner proficiency" levels in MI (as defined by the MITI criteria) was achieved, ranging from 73.9 % for the 'MI adherent behaviour' variable in the pregnancy phase to 6.7 % for 'percentage of questions coded as open' in the infancy phase. Conclusions The results suggest that it is possible to deliver a structured programme in an MI-consistent way. However, some of the behaviours regarded as key to MI practice such as the percentage of questions coded as open can be more difficult to achieve in such a context. This is an important consideration for those involved in designing effective structured interventions with an MI-informed approach and wanting to maintain fidelity to both MI and the structured programme. Trial registration Current Controlled TrialsISRCTN23019866 Registered 20/4/2009.